Honey bee diet in intensive farmland habitats reveals an unexpectedly high flower richness and a major role of weeds. Issue 4 (1st June 2015) - Requier, Fabrice; Odoux, Jean-François; Tamic, Thierry; Moreau, Nathalie; Henry, Mickaël; Decourtye, Axel; Bretagnolle, Vincent
Abstract : In intensive farmland habitats, pollination of wild flowers and crops may be threatened by the widespread decline of pollinators. The honey bee decline, in particular, appears to result from the combination of multiple stresses, including diseases, pathogens, and pesticides. The reduction of semi‐natural habitats is also suspected to entail floral resource scarcity for bees. Yet, the seasonal dynamics and composition of the honey bee diet remains poorly documented to date. In this study, we studied the seasonal contribution of mass‐flowering crops (rapeseed and sunflower) vs. other floral resources, as well as the influence of nutritional quality and landscape composition on pollen diet composition over five consecutive years. From April to October, the mass of pollen and nectar collected by honey bees followed a bimodal seasonal trend, marked by a two‐month period of low food supply between the two oilseed crop mass‐flowerings (ending in May for rapeseed and July for sunflower). Bees collected nectar mainly from crops while pollen came from a wide diversity of herbaceous and woody plant species in semi‐natural habitats or from weeds in crops. Weed species constituted the bulk of the honey bee diet between the mass flowering crop periods (up to 40%) and are therefore suspected to play a critical role at this time period. The pollen diet composition was related to the nutritional value of the collected pollen and by the local landscape composition. Our study highlights (1) a food supply depletion period of both pollen and nectar resources during late spring, contemporaneously with the demographic peak of honey bee populations, (2) a high botanical richness of pollen diet, mostly proceeding from trees and weeds, and (3) a pollen diet composition influenced by the local landscape composition. Our results therefore support the Agri‐Environmental Schemes intended to promote honey bees and beekeeping sustainability through the enhancement of flower availability in agricultural landscapes.